Superconducting properties of a two-dimensional doped semiconductor - Loktev, V.M.; Turkowski, V. (Физика низких температур, 2010)
In this paper, we study the superconducting properties of a two-dimensional model with an additional (insulating) gap Δins, which depends on temperature and doping. In particular, we study the doping evolution of the Berezinskii–Kosterlitz–Thouless critical temperature Tc and the superconducting pseudogap temperature TMFc at different values of Δins by taking into account the hydrodynamic fluctuations of the superconducting order parameter. We demonstrate that the presence of the gap Δins affect the values of the superconducting gap and temperatures Tc and TMFc in the region of the carrier densities where the gap Δins approaches to zero. In particular, the derivatives of these quantities have a jump in this region. We discuss possible relevance of the results to high-temperature superconductors.